Health Care and Community-based Interventions for War-traumatized People in Croatia : Community-based Study of Service Use and Mental Health - Frančišković, Tanja (Array, 2008)
To explore the use of health care and community-based services in war-affected regions of Croatia and its relation to mental health. A sample of 719 adults exposed to at least one war-related traumatic event were selected by random-walk technique from three Croatian counties and interviewed for socio-demographic data, mental health status (Mini International Neuropsychiatric Interview), and service use (Matrix for the Assessment of Community and Healthcare Services) in the period from 1991 to 2006. Descriptive analysis of service use was performed. Relations between service use, current mental health, and recovery from posttraumatic stress disorder (PTSD) were analyzed using logistic regression models. The traumatized population used a wide range of health care and community-based services. Health care was the most frequently used service category, especially primary health care (92.5%), followed by accommodation support (57.9%), financial support (57.7%), and employment support (32.5%). Compared with participants without mental disorders, participants with current PTSD were more likely to use only legal support (odds ratio [OR], 2.15 ; 95% confidence interval [CI], 1.15-3.99), while participants with other mental disorders were more likely to use social support and contacts (OR, 1.72 ; 95% CI, 1.08-2.75). Receiving accommodation support (OR, 2.05 ; 95% CI, 1.03-4.06) was the only significant predictor of recovery from PTSD, while seeking legal support (OR, 0.28 ; 95% CI, 0.08-0.92) was related to slower recovery. Although a wide range of services were organized to help the traumatized population in Croatia, only the solution of housing issue significantly predicted recovery. The organization of help services should take into consideration the existing infrastructure and local specificities, and respect the needs of people in war-affected areas.